Peningkatan Hasil Belajar Matematika Melalui Model Problem Based Learning Kelas 1 SDN Krasak 01 - Rosita, Ita (Universitas Sebelas Maret, 2020)
This study aims to determine the improvement of students' learning outcomes through problem based learning methods. The subjects in this study were grade 1 sdn Krasak 01 which consisted of 15 girls 5 boys. Kkm standard 65 out of 20 children only 7 students or 45.5% who reached a value of 65 and above while 13 students or 54.5% got a score below KKM. The results showed that the improvement of students' learning outcomes through problem based learning model. In pre-cycles obtained an average score of 61.5% then increased in cycle 1 with a score of 65%, increased back in the second cycle 69%. From the results of the research, it can be concluded that the problem based learning model can improve the students of SDN Krasak 01.